Bioengineering Methods in MicroRNA-Mediated Direct Reprogramming of Fibroblasts Into Cardiomyocytes - Paoletti, Camilla; Chiono, Valeria (Frontiers in Cardiovascular Medicine, 2021)
Ischemic heart disease is the major cause of mortality worldwide. Despite the most recent pharmacological progresses, cardiac regeneration is yet not possible, and heart transplantation is the only therapeutic option for end-stage heart failure. Traditional cardiac regenerative medicine approaches, such as cell therapies and tissue engineering, have failed in the obtainment of human functional cardiac tissue, mainly due to unavailability of high quantities of autologous functional cardiomyocytes (CMs), low grafting efficiency, and/or arrhythmic events. Direct reprogramming (DR) of fibroblasts into induced CMs (iCMs) has emerged as a new promising approach for myocardial regeneration by in situ transdifferentiation or providing additional CM source for cell therapy. Among available DR methods, non-viral transfection with microRNAs (miRcombo: miR-1, miR-133, miR-208, and miR-499) appears promising for future clinical translation. MiRcombo transfection of fibroblasts could be significantly improved by the development of safe nanocarriers, efficiently delivering their cargo to target cells at the required stoichiometric ratio and overall dose in due times. Newly designed in vitro 3D culture microenvironments, providing biomimetic biophysical and biochemical stimuli to miRcombo-transfected cells, significantly increase the yield of fibroblast transdifferentiation into iCMs, enhancing CM gene expression. Epigenetic regulation of gene expression programs, critical to cell lineage commitment, can also be promoted by the administration of specific anti-inflammatory and anti-fibrotic soluble factors, helping in suppressing fibroblast signature. The aim of this mini-review is to introduce the readers to a relatively unknown field of cardiac research integrating bioengineering tools as relevant for the progress of miRNA-mediated cardiac DR.